The use of human amniotic fluid stem cells as an adjunct to promote pulmonary development in a rabbit model for congenital diaphragmatic hernia. (19th June 2015) - DeKoninck, Philip; Toelen, Jaan; Roubliova, Xenia; Carter, Shea; Pozzobon, Michela; Russo, Francesca Maria; Richter, Jute; Vandersloten, Pieter‐Jan; Verbeken, Erik; De Coppi, Paolo; Deprest, Jan
<x xml:space="preserve">Abstract</x> What's already known about this topic? There is increasing evidence that cell therapy using mesenchymal stem cells could have a beneficial effect in treating adult lung disease. Amniotic fluid stem cells are a population of cells with multipotent differentiation capacities. Initial reports in rodent CDH models have shown promising evidence using these cells to improve pulmonary development in utero. What does this study add? Intra‐tracheal cell therapy with amniotic fluid stem cells in combination with tracheal occlusion in a rabbit CDH model increases the number of alveoli, without major signs of toxicity.